Teaching the Future: AI Awareness, Attitudes, and Curriculum Readiness among Healthcare Students and Faculty in Pakistan. - Bushra Madad Ali; Ayesha Rayyan; Saman Riaz; Fizza Ikram; Saira Sarfaraz (International Journal of Endorsing Health Science Research, 2025)
Background: Artificial intelligence (AI) is rapidly transforming healthcare delivery, creating new demands for AI literacy and curriculum readiness in health professions education. Yet, in Pakistan, structured integration of AI into medical and allied health curricula remains limited. This study assessed awareness, perceptions, and attitudes toward AI among healthcare students and faculty in Pakistan, highlighting similarities, differences, and barriers to curricular integration. Methodology: A descriptive cross-sectional survey was conducted among 105 students and 50 faculty members from medical, dental, pharmacy, nursing, and physiotherapy institutions across Pakistan. A structured online questionnaire, adapted from a validated instrument, was used to collect data on demographics, AI awareness, and attitudes. Descriptive statistics, Chi-square tests, and Mann–Whitney U tests were employed, with effect sizes reported. Results: Both groups reported high awareness of AI, primarily through social media (84.8% students, 86.0% faculty). A basic understanding of AI was acknowledged by 65.7% of students and 74.0% of faculty. Students were slightly more positive about AI’s role in improving healthcare (median=5 vs. 4; p=0.04, small effect). Faculty placed significantly greater importance on AI for clinical decision support (median=5 vs. 4; p=0.01, moderate effect). Divergence was observed in training priorities, with students favoring patient-centered applications and faculty emphasizing teaching applications. Despite these differences, both groups strongly supported AI inclusion in medical education. Conclusion: Students and faculty in Pakistan recognize the relevance of AI in healthcare and education, but subtle differences in emphasis highlight the need for tailored training strategies. The findings underscore the importance of structured AI literacy initiatives, faculty development, and policy-level curriculum integration to bridge gaps in preparedness for an AI-enabled healthcare system.